Experimental Archaeology and the Denticulate Mousterian - Karen Arnold (Papers from the Institute of Archaeology, 1991)
The following· essay is a summary of preliminary experimental work carried out in connection with my doctoral research on the nature of the Denticulate Mousterian facies, which was presented to the postgraduate seminar of the Institute of Archaeology, UCL on October 24th 1990.
Keywords: neanderthal; neanthertal; flint; tools; denticulates; mousterian